Mrs. Jemimah Gecaga speaking to attendees at the YWCA meeting - Unknown:::Creator::::::::::::
Photograph shows Mrs. Jemimah Gecaga, Kenya YWCA president, speaking to men and women attending the 1965 YWCA annual meeting in San Jose, California. Mrs Sargent (Lucille) Wright is seated to the left of the microphone.